2013
DOI: 10.1002/jor.22317
|View full text |Cite
|
Sign up to set email alerts
|

Shape optimization for the subsidence resistance of an interbody device using simulation‐based genetic algorithms and experimental validation

Abstract: Subsidence of interbody devices into the vertebral body might result in serious clinical problems, especially when the devices are not well designed and analyzed. Recently, some novel designs were proposed to reduce the risk of subsidence, but those designs are based on the researcher's experience. The purpose of this study was to discover the interbody device design with excellent subsidence resistance by changing the device's shape. The three-dimensional nonlinear finite element models, which consisted of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Finally, cage subsidence risk has been predicted based on contact pressures [11], Von Misses stresses [8] and 282 total reaction force [12]. However, none of these outcomes account for bone failure which is the actual cause of Contrary to other studies which found more inelastic strains in extension or lateral bending, in our model plastic 299 strains were more prone to occur in the anterior part of the caudal vertebra during flexion.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Finally, cage subsidence risk has been predicted based on contact pressures [11], Von Misses stresses [8] and 282 total reaction force [12]. However, none of these outcomes account for bone failure which is the actual cause of Contrary to other studies which found more inelastic strains in extension or lateral bending, in our model plastic 299 strains were more prone to occur in the anterior part of the caudal vertebra during flexion.…”
mentioning
confidence: 89%
“…On the other hand, cage characteristics such as shape, material and positioning are also expected to have a 80 significant influence on surgery success. Previous studies have used finite element (FE) models to compare 81 among commercial cages, but only some of them have discussed the influence of cage material [11] or shape 82 [8,12] using parametric or optimization methods. In their study, Hsu et al…”
mentioning
confidence: 99%
“…For example, Willing and Kim kept the mesh element count low enough for successful completion of analysis 43. Likewise, Hsu performed parametric optimisation of spine interbody fusion device to improve their subsidence resistance and this required simplification of loading conditions and geometry 27. Finally, the FE model must be robust enough to allow changes to its design parameters during optimisation.…”
Section: Introductionmentioning
confidence: 99%
“…Cage subsidence has been reported [27,28], and this complication was related to cage design [22,29]. The present study applied a simulation-based genetic algorithm to determine an optimum AM cage shape.…”
Section: Discussionmentioning
confidence: 98%
“…To maximize the total reaction force of the AM cage, a simulation-based genetic algorithm was used in the present study. This algorithm had been successfully developed to discover an interbody device design with the highest subsidence resistance [22]. Both the finite element model and the genetic algorithm were directly developed in ANSYS 16.2 (ANSYS, Inc., Canonsburg, PA, USA) using the ANSYS ® Parametric Design Language (APDL).…”
Section: Shape Optimizations For Subsidence Resistance Of Am Cagesmentioning
confidence: 99%